2017
DOI: 10.1038/nm.4422
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neuron–associated macrophages contribute to obesity by importing and metabolizing norepinephrine

Abstract: The cellular mechanism(s) linking macrophages to norepinephrine (NE)-mediated regulation of thermogenesis have been a topic of debate. Here we identify sympathetic neuron-associated macrophages (SAMs) as a population of cells that mediate clearance of NE via expression of solute carrier family 6 member 2 (SLC6A2), an NE transporter, and monoamine oxidase A (MAOA), a degradation enzyme. Optogenetic activation of the sympathetic nervous system (SNS) upregulates NE uptake by SAMs and shifts the SAM profile to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
397
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(421 citation statements)
references
References 48 publications
23
397
0
1
Order By: Relevance
“…These findings were disputed in a multilaboratory paper providing strong evidence that WAT macrophages cannot express TH and therefore can't produce catecholamines to beige WAT [97], which called into question the upstream role of eosinophils in beiging as well. Additional studies have provided further insight by revealing the presence of nerve-associated macrophages (NAMs/SAMs) that line TH-producing sympathetic nerves within WAT [98,99]. It was found that the NAMs/SAMs could collect and catabolize catecholamines secreted by nerves, and in this way modulate the available pool of catecholamines that could otherwise act on proximal adipocytes (Figure 1).…”
Section: Macrophages In Wat Type 2 Inflammation: Caveats and Controvementioning
confidence: 99%
“…These findings were disputed in a multilaboratory paper providing strong evidence that WAT macrophages cannot express TH and therefore can't produce catecholamines to beige WAT [97], which called into question the upstream role of eosinophils in beiging as well. Additional studies have provided further insight by revealing the presence of nerve-associated macrophages (NAMs/SAMs) that line TH-producing sympathetic nerves within WAT [98,99]. It was found that the NAMs/SAMs could collect and catabolize catecholamines secreted by nerves, and in this way modulate the available pool of catecholamines that could otherwise act on proximal adipocytes (Figure 1).…”
Section: Macrophages In Wat Type 2 Inflammation: Caveats and Controvementioning
confidence: 99%
“…In bone metastasis, sympathetic signaling via activation of β 2 ‐AR on osteoblasts leads directly to cancer cell recruitment and indirectly to vascular changes that promote colonization of metastatic cancer cells in the bone marrow . Last, NE uptake by bone and immune cells may also contribute to extraneuronal control of local NE homeostasis and actions on the skeleton …”
Section: Molecular Signals From Neurons To Bone—neurotransmittersmentioning
confidence: 99%
“…However, it is difficult to determine whether these ganglia are part of the SNS, owing to the lack of tyrosine hydroxylase (TH) counterstaining in these studies. Sympathetic thoracic chain ganglia innervating WAT were recently described in mice using TH-specific antibody staining 211 . Thus, coupling tract tracers and retrograde labelling to TH immunostaining will be useful to further determine the nature of the SNS ganglia projection to adipose tissues.…”
Section: Figurementioning
confidence: 99%
“…4). However, there is a caveat associated with PRV tracing studies: glial or phagocytic cells of the immune compartment might accumulate PRV particles, populate the SNS ganglia and be incorrectly interpreted as neurons 211 . Moreover, studies in rats failed to identify innervation of inguinal BAT from ganglion cells in the T13 and the L1–L3 ganglia 110 , again reinforcing the need for further investigations into species-specific innervation differences.…”
Section: Figurementioning
confidence: 99%